Foundations of human resource development - Swanson, Richard A., 1942-; Holton, Elwood F., 1957- (San Francisco : Berrett-Koehler, 2009)
Here, leading scholars in the field present an essential guidebook for the human resource development profession. Drawing on an extensive knowledge base, Swanson and Holton update their classic single volume compilation of the foundational materials of the profession.
Human resource development as a professional field of practice -- Introduction to human resource development models and processes -- History of human resource development -- Role of theory and philosophy in human resource development -- Theory of human resource development -- Component theories of human resource development -- Paradigms of human resource development -- Perspectives on performance in human resource development -- Perspectives on learning in human resource development -- Overview of training and development -- The nature of expertise -- Training and development practices -- Overview of organization development -- The nature of the change process -- Organization development practices -- Strategy and human resource development -- Accountability in human resource development -- Human resource development policy and planning -- Globalization and human resource development -- Technology and human resource development -- Challenges facing human resource development.
Includes bibliographical references (p. 461-505) and indexes.
Keywords: Employees -- Training of; Personnel management; Manpower planning; Human capital